SEISMICITY STUDY OF KELUD VOLCANO ON OCTOBER 2007 - (NIM 12403026), MUHAIMININ
Seismicity of Kelud Volcano increased continuously in September and reached the peak at October 2007 indicated by hundred volcanic earthquakes which recorded at four stations. To reduce the noises, a band pass filter with range 3 - 15 Hz was applied to the seismogram data recorded from October 1st till 31st 2007. The hypocenters are estimated using arrival times of P and S waves which are easier to pick in the filtering data. The local magnitude (ML) at each station is calculated using its maximum amplitude. Among local magnitude formulations, in this study, we use the formulation developed by Del Pezzo and Petrosino (2001) applied to Mount Vesuvius data. The final magnitude is the average value from four magnitudes values. The results show that the hypocenters are distributed in depth 0-20 km with magnitude range from -3.44 to 1.52 in Richter scale. The strong events whose magnitude 0.1-1.33 at depth 14-20 km are generated by cracks which are caused by magma pressure from magma chamber. The events whose magnitude from -2.97 until 1.46, in NW-SE direction are placed at 2-10 km depth, meanwhile the events whose magnitude from -3.41 until 1.17 at NE-SW direction are at 2-12 km depth. Those events are about along two normal faults in this volcano. Of course, those events are caused by dislocation of those faults. The events with relatively low magnitude beneath the crater are caused by the friction between the magma and the conduit when the magma flows to the surface.